THE INFLUENCE OF PERCEPTIONS OF THE USE OF VIDEO MEDIA ON STUDENTS' LEARNING INDEPENDENCE IN THE CLASS XI PAI SUBJECT OF SMA NEGERI 6 SINJAI - Munawaroh, Munawaroh; Ismail, Muh. Ilyas; Ista, Akbar (JICSA : Journal of Islamic Civilization in Southeast Asian, 2024)
This research discusses the influence of perceptions of using video media on students' learning independence in Class XI PAI subjects at Sinjai State High School. This research uses a quantitative type of research method ex-post facto. Respondents in this study totaled 61 people who were obtained using Proporsional cluster random sampling, to collect data using a questionnaire instrument which was analyzed using descriptive and inferential statistics. The results of research using SPSS 24 obtained analysis results = 216 dan P-value= 000/2= 0 < 0,05, this means that Ho is rejected and Ha is accepted. Thus, it can be concluded that "The perception of the use of video media has a positive effect on the learning independence of students in PAI subjects at SMA Negeri 6 Sinjai" with a contribution of 60% are in the medium category while the remaining 40% are influenced by other factors outside of the variables. Influence The perception of using video media has had a significant impact on students at SMA Negeri 6 Sinjai besides aims to develop students' cognitive, affective and psychomotor aspects, it can also stimulate and attract students' attention to learning. Apart from that, this media also conveys information while influencing students' emotions and attitudes.